2006
DOI: 10.1148/rg.264055212
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Standard-Compliant Audience Response System for Medical Education

Abstract: Audience response systems (ARSs) have been suggested as a means to improve the effectiveness of didactic lectures, but their widespread use has been limited because of cost and complexity. The authors developed a simple, cost-effective ARS that relies completely on standard networking technology, is embedded easily into a PowerPoint presentation, and operates without the need for extensive server setup and configuration. A PowerPoint Add-in that capitalizes on WiFi (wireless fidelity) technology was created th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 4 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…Theoretically, the system could be used to transmit answers while at home taking an online class or while watching a webcast lecture. Students can also use the internet to submit answers during a live lecture using WiFi (wireless fidelity) technology such as pocket/notebook/laptop/desktop personal computers, handheld video game consoles, or cell phones as well as non-WiFi Web-enable Windows Mobile 1 devices or BlackBerry 1 smartphones (Research in Motion, Waterloo, Ontario, Canada), (Streeter and Rybicki, 2006;TurningPoint, 2009). Interestingly, these recent developments in ARS methodology where a student can remotely participate in education activity without being physically present in the classroom are congruent with the opinions of our students who indicated that ARS had no impact on their decision to attend classes.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the system could be used to transmit answers while at home taking an online class or while watching a webcast lecture. Students can also use the internet to submit answers during a live lecture using WiFi (wireless fidelity) technology such as pocket/notebook/laptop/desktop personal computers, handheld video game consoles, or cell phones as well as non-WiFi Web-enable Windows Mobile 1 devices or BlackBerry 1 smartphones (Research in Motion, Waterloo, Ontario, Canada), (Streeter and Rybicki, 2006;TurningPoint, 2009). Interestingly, these recent developments in ARS methodology where a student can remotely participate in education activity without being physically present in the classroom are congruent with the opinions of our students who indicated that ARS had no impact on their decision to attend classes.…”
Section: Discussionmentioning
confidence: 99%
“…The students then select their choice using the ARS response card keypad (referred to as ''clickers'') and the percentage of students selecting each multiple-choice answer is immediately displayed on the PowerPoint slide. 2 The instructor and the class see the responses displayed as aggregated results and individual's responses are not identified. The displayed results provide immediate feedback to students about content mastery while in lecture, which allows instructors to remediate or reinforce concepts during the class session without singling out individual students.…”
Section: Introductionmentioning
confidence: 99%
“…Audience response systems (ARSs) are tools to facilitate active learning that can increase audience participation in the classroom and assess learning in real time (22,23). ARSs allow the teacher to gauge where the learners are as a whole, what areas they may be struggling with, and in turn, what issues need to be addressed immediately.…”
Section: Audience Response Systemmentioning
confidence: 99%